COVID‐19 encephalopathy: Clinical and neurobiological features. Issue 7 (23rd April 2021) - Uginet, Marjolaine; Breville, Gautier; Assal, Frédéric; Lövblad, Karl‐Olof; Vargas, Maria Isabel; Pugin, Jérôme; Serratrice, Jacques; Herrmann, Francois R.; Lalive, Patrice H.; Allali, Gilles
Abstract: Severe acute respiratory coronavirus 2 (SARS‐CoV‐2) has been associated with neurological complications, including acute encephalopathy. To better understand the neuropathogenesis of this acute encephalopathy, we describe a series of patients with coronavirus disease 2019 (COVID‐19) encephalopathy, highlighting its phenomenology and its neurobiological features. On May 10, 2020, 707 patients infected by SARS‐CoV‐2 were hospitalized at the Geneva University Hospitals; 31 (4.4%) consecutive patients with an acute encephalopathy (64.6 ± 12.1 years; 6.5% female) were included in this series, after exclusion of comorbid neurological conditions, such as stroke or meningitis. The severity of the COVID‐19 encephalopathy was divided into severe and mild based on the Richmond Agitation Sedation Scale (RASS): severe cases ( n  = 14, 45.2%) were defined on a RASS < −3 at worst presentation. The severe form of this so‐called COVID‐19 encephalopathy presented more often a headache. The severity of the pneumonia was not associated with the severity of the COVID‐19 encephalopathy: 28 of 31 (90%) patients did develop an acute respiratory distress syndrome, without any difference between groups ( p  = .665). Magnetic resonance imaging abnormalities were found in 92.0% (23 of 25 patients) with an intracranial vessel gadolinium enhancement in 85.0% (17 of 20 patients), while an increased cerebrospinal fluid/serum quotient of albumin suggestive of blood‐brain barrier disruption was reported in 85.7% (6 of 7 patients). Reverse transcription‐polymerase chain reaction for SARS‐CoV‐2 was negative for all patients in the cerebrospinal fluid. Although different pathophysiological mechanisms may contribute to this acute encephalopathy, our findings suggest the hypothesis of disturbed brain homeostasis and vascular dysfunction consistent with a SARS‐CoV‐2‐induced endotheliitis.